2000
DOI: 10.1103/physrevlett.85.3664
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Near-Surface Structural Phase Transition inSrTiO3by Optical Second Harmonic Generation

Abstract: A near-surface structural phase transition on a SrTiO3 single crystal, occurring at T(*) about 45 K above the bulk cubic-to-tetragonal transition, is observed by means of optical second harmonic generation. The temperature dependence of the second harmonic field in the vicinity of T(*) is described with a phenomenological Landau-type model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
54
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 17 publications
(14 reference statements)
7
54
1
1
Order By: Relevance
“…20 Subsequent experimental studies using transmission electron microscopy 22 and second harmonic generation (SHG) confirmed such wall polarity. 23,24 Similar behavior was attributed to multidomain boundaries with distinct polar and oxygen octahedral tilting in BiFeO 3 ab initio simulations. 25 The latest experimental advance was reported 26 in resonant piezoelectric spectroscopy (RPS) experiments for strontium titanate at cryogenic temperatures, well below the ferroelastic transition (105 K).…”
mentioning
confidence: 56%
“…20 Subsequent experimental studies using transmission electron microscopy 22 and second harmonic generation (SHG) confirmed such wall polarity. 23,24 Similar behavior was attributed to multidomain boundaries with distinct polar and oxygen octahedral tilting in BiFeO 3 ab initio simulations. 25 The latest experimental advance was reported 26 in resonant piezoelectric spectroscopy (RPS) experiments for strontium titanate at cryogenic temperatures, well below the ferroelastic transition (105 K).…”
mentioning
confidence: 56%
“…The phase transition involves the rotation of TiO 6 octahedra and has been featured as a classic example of a soft mode phase transition [24]. There have been conflicting reports [17][18][19][20][21][27][28][29] that a surface phase transition may occur at significantly higher temperature ~ 150 K and a second bulk phase transformations below ~70 K [25,26]. The "surface" structures of SrTiO 3 reported in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a near-surface structural PT on a STO single crystal, occurring at T Ã at about 45 K above the bulk cubic-totetragonal transition, was reported on the base of optical second harmonic generation (SHG) experiments [23]. The temperature dependence of the second harmonic field is described using a phenomenological Landau-type model.…”
Section: Afd Cmentioning
confidence: 99%
“…[24], temperature dependence of the surface order parameter h 0 as well as of the surface transition temperature T S calls for taking into account surface-induced terms in the expression for the free energy. Following Levanyuk and Minyukov [24] this gives, for the second order PT [23]:…”
Section: Afd Cmentioning
confidence: 99%